2012
DOI: 10.1186/1758-3284-4-28
|View full text |Cite|
|
Sign up to set email alerts
|

Squamous cell carcinoma of the oral cavity and the oropharynx in patients less than 40 years of age: a 20-year analysis

Abstract: BackgroundSquamous cell carcinoma mainly afflicts patients older than 40 years of age however, few cases are seen in younger patients. The aim of this study therefore was to determine the incidence of squamous cell carcinoma of the oral cavity and oropharynx in patients less than 40 years of age with a view to assessing the prognosis over a period of time.MethodsThis was a 20 years retrospective review of patients who were histologically diagnosed with squamous cell carcinoma of the oral cavity and the orophar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
52
4
8

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 25 publications
15
52
4
8
Order By: Relevance
“…Different results were published by some studies (19,22) , in which there was predominance on the floor of mouth, followed by the tongue, what indicates a slight difference from previous researches with young individuals (9,17) . This discrepancy in results about the anatomical site may happen due to the sample size in each study, and to the most frequent harmful habits in the studied population.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…Different results were published by some studies (19,22) , in which there was predominance on the floor of mouth, followed by the tongue, what indicates a slight difference from previous researches with young individuals (9,17) . This discrepancy in results about the anatomical site may happen due to the sample size in each study, and to the most frequent harmful habits in the studied population.…”
Section: Discussioncontrasting
confidence: 45%
“…That imposes limitation on comparison and analysis of results. On the other hand, the majority of the studies considered individuals under 40 young and belonging to a special group of patients affected by OSCC (3,9,17,22) , which tends to affect mainly patients in the fifth and sixth decades of life (9) . OSCC occurs more frequently in males.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies from India and across reported that most of OSCC cases diagnosed as moderately differentiated OSCC (Ayaz et al, 2011;Udeabor et al, 2012). The clinico-pathological factor that influence the treatment outcome and likelihood of recurrence are advanced T stage or stage III-IV disease at diagnosis, including local regional nodal involvement, positive resection margins or the resection margins being very close to the tumor and thickness of tumor ≥7mm (Battoo et al, 2012;Hakeem et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…In today's time there are 4% to 13% of the cases of oral squamous cell carcinoma that affects subjects younger than 45 years of age. [4][5][6][7][8][9][10] The most frequently affected site is tongue and it is seen generally amongst alcohol and tobacco users. 4,5 Squamous cell carcinoma of lower lip is generally seen amongst subjects with exposure to sunlight.…”
Section: Introductionmentioning
confidence: 99%
“…6 There has been differences in the etiological factors that are responsible for causing oral squamous cell carcinoma amongst young and elderly individuals as the young individuals are exposed to the risk factors like sunlight and tobacco for a short period of time. 9,[11][12][13][14][15] Oral squamous cell carcinoma occurring amongst the younger individuals have an increased aggressiveness and poor clinical prognosis when compared to those affecting the elderly subjects. 6,7,12,16,17 The prognosis of the condition is determined by the prognostic factors that would in turn determine the biological aggressiveness of the condition amongst the subjects.…”
Section: Introductionmentioning
confidence: 99%